2009
DOI: 10.2337/db09-0033
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages and Adipocytes in Human Obesity

Abstract: OBJECTIVEWe investigated the regulation of adipose tissue gene expression during different phases of a dietary weight loss program and its relation with insulin sensitivity.RESEARCH DESIGN AND METHODSTwenty-two obese women followed a dietary intervention program composed of an energy restriction phase with a 4-week very-low-calorie diet and a weight stabilization period composed of a 2-month low-calorie diet followed by 3–4 months of a weight maintenance diet. At each time point, a euglycemic-hyperinsulinemic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
131
5
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(149 citation statements)
references
References 45 publications
10
131
5
3
Order By: Relevance
“…In line, our previous study showed a downregulation of both pro-inflammatory (for example, human leukocyte antigen-D region, osteopontin) and antiinflammatory (for example, interleukin-10) genes. 33 These findings favor 'the balanced macrophage activation hypothesis' that explains macrophage activation as a complex of cyclic processes to keep balance between pro-and Human adipose tissue macrophages during diet M Kováčiková et al anti-inflammatory states in inflamed tissue. 49 In the mouse, high-fat diet induces a recruitment of ATM with M1 properties and no change in M2 macrophages.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In line, our previous study showed a downregulation of both pro-inflammatory (for example, human leukocyte antigen-D region, osteopontin) and antiinflammatory (for example, interleukin-10) genes. 33 These findings favor 'the balanced macrophage activation hypothesis' that explains macrophage activation as a complex of cyclic processes to keep balance between pro-and Human adipose tissue macrophages during diet M Kováčiková et al anti-inflammatory states in inflamed tissue. 49 In the mouse, high-fat diet induces a recruitment of ATM with M1 properties and no change in M2 macrophages.…”
Section: Discussionmentioning
confidence: 97%
“…33 Indeed, in the VLCD phase, there was an increase or no change in inflammation-and macrophagerelated genes. At the end of the whole dietary program, there was a coordinated downregulation of these genes including CD14, CD68 and CD163, as shown in this study.…”
Section: Discussionmentioning
confidence: 99%
“…13,48 In addition to cachexia, feeding a low-calorie diet has very recently been found in microarray studies to lead to a modest increase ZAG and adiposity C Bing et al in ZAG mRNA level in subcutaneous adipose tissue of obese women. 49 ZAG is also implicated in the development of adipose tissue by our recent study in rats during the first month after birth, in which ZAG protein levels were reduced at weaning when there is a large increase in fat mass. 50 A downregulation of ZAG expression in obesity has recently been reported in mice as well as in humans.…”
Section: Zag Expression and Body Fat Massmentioning
confidence: 91%
“…RNA analysis Total RNA isolation was performed as previously described [32]. The mRNA expression of macrophage-specific genes was assessed by reverse transcription and real-time quantitative PCR using a sequence detection system (ABI PRISM 7900; Applied Biosystems, Foster City, CA, USA) and custom TaqMan low-density arrays and TaqMan gene expression assay pre-loaded targets (both from Applied Biosystems).…”
Section: Methodsmentioning
confidence: 99%